WORKSHOP HIGHER ORDER THINGKING SKILLS BAGI GURU SMK DI DKI JAKARTA - Uswatun Hasanah; Agus Dudung; Sugeng Priyanto (Bahasa Indonesia, 2017)
ABSTRACT: The purpose of this Activity is to provide good quality HOT test quality training seen from: (a) Validity and reliability of the test (b) Grain analysis to see the difficulty index and Different power. Target Audience in this activity is the teachers of SMK in Jakarta, who really interested and have the potential to develop. The number of active participants is 25 vocational teachers. The participant will then transfer the training activities to the other teachers through each school. The type of activity material is this training theory and practice, with 20% theory composition and 80% practice covering aspects of data analysis techniques with computer assistance through SPSS program and ITEMAN program. Theory is given before engaging in practical activities or integrated during the direct practice by the participants. Based on the results of the exercises made some conclusions. There are two aspects of training materials provided to teachers in Jakarta, namely the technical aspects of HOT problem making skills and aspects of ITEMAN program use. Based on the evaluation that has been implemented, from the technical aspect, this training can be quite successful. Over 90% of participants mastered the material well, this training can be quite successful. Given the time of limited service activities. Nevertheless, in general, this service activity received a positive response from the teachers especially trainees, and schools in general. In relation to the implementation of this activity, suggestions may be made: (a) For the trainee's teachers, the knowledge and skills possessed should be developed on their own. The way that can be taken for example, teaching in a relavan. (b) For the implementing team of dedication activities, to be considered for holding the same training but with more in-depth material in the coming year. The goal is to achieve the desired end goal. namely to make the professional teachers in the field. (c) It is good that teachers continue to develop practical practices in schools. ABSTRAK: Tujuan Kegiatan ini adalah Untuk memberikan pelatihan pembuatan kualitas tes HOT yang baik dilihat dari: (a) Validitas dan reliabilitas tes (b) Analisis butir untuk melihat indeks kesukaran dan Daya beda. Khalayak Sasaran dalam kegiatan ini adalah para Guru SMK di Jakarta, yang betul-betul berminat dan mempunyai potensi untuk berkembang. Jumlah peserta yang aktif adalah 25 Guru SMK. Peserta itu nantinya akan mentransfer kegiatan pelatihan tersebut ke para guru yang lainnya lewat masing-masing sekolah. Jenis materi kegiatan adalah pelatihan ini teori dan praktek, dengan komposisi 20% teori dan 80% praktek yang mencakup aspek teknik analisis data dengan bantuan komputer melalui program SPSS dan program ITEMAN. Teori diberikan sebelum melakukan kegiatan praktek atau diintegrasikan selama praktek langsung oleh peserta. Berdasarkan hasil latihan yang dilakukan didapat beberapa kesimpulan, Terdapat dua aspek materi pelatihan yang diberikan terhadap para guru di Jakarta, yaitu aspek teknik keterampilan pembuatan soal HOT dan aspek penggunaan program ITEMAN. Berdasarkan evaluasi yang telah dilaksanakan, dari aspek teknik, pelatihan ini dapat dikatakan cukup berhasil. Lebih dari 90% peserta menguasai materi dengan baik, pelatihan ini dapat dikatakan cukup berhasil. Mengingat waktu kegiatan pengabdian yang terbatas. Namun demikian secara umum kegiatan pengabdian ini mendapat respons yang positif dari para guru peserta pelatihan khususnya, dan sekolah pada umumnya. Berkaitan dengan pelaksanaan kegiatan ini, saran yang dapat disampaikan: (a) Bagi para guru peserta latihan, bekal pengetahuan dan keterampilan yang telah dimiliki ini hendaknya dikembangkan sendiri. Cara yang dapat ditempuh misalnya, mengajar dibidang yang relavan. (b) Bagi tim pelaksana kegiatan pengabdian, supaya dipertimbangkan untuk mengadakan pelatihan yang sama namun dengan materi yang lebih mendalam di tahun mendatang. Tujuannya adalah agar tercapainya tujuan akhir yang diharapkan. yaitu menjadikan para guru yang professional pada bidangnya. (c) Ada baiknya para guru tetap mengembangkan latihan-latihan praktik di sekolah.